Analis Puisi Stopping By Woods On The Snowy Evening Byrobert Frost: Aspek Grammar dan Level Fonologi - Ihsan, Pramudana (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
Abstrak: Robert Frost memenangkan empat Hadiah Pulitzer dengan puisi ini, Stopping by Woods on The Snowy Evening bukanlah puisi biasa yang ditulis untuk sebuah kesempatan biasa. Puisi ini penuh makna yang harus diungkapkan dan dianalisis.Banyak kritikus memiliki persepsi yang berbeda sesuai dengan arti sebenarnya dari karya agung ini.Penulis mencoba menganalisis puisi ini dari analisis tingkat grammatical, analisis bahasa figuratif yang mengandung tingkat fonologis dan gambaran analisis wicara.Analisis ini bertujuan untuk mengungkapkan setiap baris puisi ini menjadi salah satu unsur diskusi sastra.Beberapa elemen puisi dan pola grammatical yang dianalisis, membentuk perspektif di otak pembaca tentang bagaimana kompleks puisi ini diciptakan.Kata Kunci: Robert Frost, Stopping by Woods on The Snowy Evening, grammatical level, Phonological levelAbstract: Robert Frost won four Pulitzer Prizes by this poem, Stopping by Woods on The Snowy Evening is not an ordinary poem which is written for an ordinary occasion. This poem is full of meanings which should to be revealed and analyzed. Many critics have different perception according the truly meaning of this great masterpiece. The writer tries to analyze this poem from analyzing tools of grammatical level, figurative language analysis containing phonological level and figure of speech analysis. These analyzing tools are purposed to reveal each line of this poem become one element of literary discussions. Several poetry elements and grammatical patterns which are analyzed, establish a perspective on the reader’s brain of how complex this poem was created.Key Words: Robert Frost, Stopping by Woods on The Snowy Evening, grammatical level, Phonological level